RIOTs in Germany: Constructing an interregional input-output table for Germany - Oliver Krebs (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2018)
Despite their importance, little is known about the spatial structure of trade and production networks within Germany and their connection to the international markets. The lack of data is problematic for regional analysis of aggregate shocks such as trade agreements and to analyze network effects of regional policies. This paper takes an in-depth look at this German production structure and trade network at the county level based on a unique data set of county level trade. I find a surprisingly vast heterogeneity with respect to specialization, agglomeration and trade partners. The paper subsequently shows how to adapt recent advances in regionalization of input-output tables to derive an interregional input output table for 402 German counties and 26 foreign partners for 17 sectors that is cell-by-cell compatible with the WIOD tables for national aggregates and can be used for impact analysis and CGE model calibration.
Keywords: R15; R12; F17; 330; Germany; regional trade; input-output tables; proportionality